PHYSICAL AND CHEMICAL CHARACTERIZATION OF IN COCONUT HUSK FIBER SUBSTRATE AFTER THE CULTIVATION OF PEPPER IN A HYDROPONIC SYSTEM WITH WATER REUSE AND DIFFERENT DEPHTS OF NUTRIENT SOLUTION - De Carvalho, Renata Da Silva Cuba [UNESP]; De Melo, Mara Rúbia Mendes [UNESP]; De Sousa, Francielly Guieiro Gomes [UNESP]; Filho, Luís Roberto Almeida Gabriel [UNESP]; Klar, Antonio Evaldo [UNESP]; Filho, Hélio Grassi [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
This work aimed to characterize the physical and chemical characteristics of the coconut husk fiber substrate before and after its use with the pepper crop, cultivated in pots with a nutritive solution prepared with reuse and drinking water and different depths of this solution replenishment (100, 75 and 50% of crop evapotranspiration). Cultivation was conducted in pots greenhouse with a volumetric capacity of 15 L, filled with coconut husk fiber. The plants were grown for 175 days and every 30 days, the pH and electrical conductivity of the substrate were measured in the laboratory. After the plants were harvested, samples of the substrate were collected and the chemical and physical characteristics were evaluated: electrical conductivity, pH, NH4+, NO3-, P, K, Ca, Mg, S, Cl, B, Fe, Mn, Cu, Zn, cation exchange capacity (CTC), water retention capacity (10kPA), and dry bulk density. The replacement of the nutrient solution in the substrate through crop evapotranspiration provided an increase in nutrient content, electrical conductivity, CTC of substrate and density. The highest values for theses parameters were verified for the treatments cultivated with nutritive solution prepared with water reuse.
CARACTERIZAÇÃO FÍSICO-QUÍMICA DE SUBSTRATO DE FIBRA DE CASCA DE COCO APÓS O CULTIVO HIDROPÔNICO DE PIMENTÃO COM ÁGUA DE REÚSO E DIFERENTES LÂMINAS DE SOLUÇÃO NUTRITIVA
Keywords: Effluent; Hydroponic; Nutrients; Salinization; Wastewater